IMPORTANCE OF NEEDS ANALYSIS IN ESP. HOW NEEDS ANALYSIS IS CONDUCTED FOR TOURISM FACULTY STUDENTS (Web of Teachers: Inderscience Research, 2023)
This paper analyzes the importance of needs assessment in ESP and how needs analysis is conducted for tourism faculty students. As it is the first step in education and it is very essential to use appropriate methods and tool in order to determine learners’ needs assessment. According to results of analysis teacher will know learners’ lacks, wants, and needs and can create learning objectives and lesson plans appropriately. In this paper several methods of data collection are given in order to analyze needs of tourism faculty students.